Global Connectivity through International Postal System - Qureshi, Hafiz Shakil Ahmed (Journal of Pakistan Administration, 2022)
Monopoly is a rare commodity in today’s world. With advancement of technology and development in means of communications and transportation, competition has become fierce. Customers have a variety of choices and there seems to be no indispensable producer or service provider. From the customers’ point of view, this positive development has brought the former era of exploitation to an end. On the other hand, it has forced organizations to face cutthroat competition and colossal challenges. This reality has prompted organizations to improve and has enhanced customers` power that in turn has ushered in efficient service delivery and quality of service.
Keywords: Global Connectivity; International Postal System; service provider; quality of service